Implications of Gamification for Student Learning Motivation: Meta-Analysis Study - Mario Emilzoli; Asep Herry Hernawan; Hanoum R. Nadia; Gema Rullyana; Zahrani Putri Saidah; Lia Susanti; Muhamad Kosim Gifari (CV Media Inti Teknologi, 2025)
Background of the study: Gamification is increasingly applied in education to stimulate engagement and motivation, yet empirical findings on its effectiveness remain mixed.Aims: This study aims to determine the overall effect of gamification on students’ learning motivation and to examine whether education level, sample size, and publication year moderate this effect.Methods: A meta-analysis was conducted using Scopus-indexed journal articles published between 2015–2024. Studies were included if they reported motivation outcomes with sample size, mean, and standard deviation. Effect sizes (Hedges’ g) were calculated and synthesized using a random-effects model with OpenMEE.Results: Twenty-five articles (26 outcomes) met the criteria. Gamification demonstrated a significant and very strong overall effect on learning motivation (ES = 1.061). Moderator analysis showed stronger effects at the senior high school level, while the influences of sample size and publication year were comparatively smaller.Conclusion: Gamification substantially enhances students’ learning motivation compared with non-gamified approaches. These results support the careful and contextual integration of gamified elements in teaching to optimize learner engagement and instructional quality.